2014
DOI: 10.1007/s00345-014-1252-2
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer at the peripheral end of prostate biopsy specimen predicts increased risk of positive resection margin after radical prostatectomy: results of a prospective multi-institutional study

Abstract: PC at the peripheral end of prostate biopsy specimen predicts an increased risk of R1 status in subsequent RP. This simple and cheap technique may contribute to an increased accuracy of risk stratification for curative treatment for PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Ponholzer et al 11 reported that marking the PE of biopsy cores and the positivity of PE could increase the risk of positive surgical margins in prostatectomy specimens. Their study involved 445 patients, of whom 174 (39.1%) had positive PE, and ultimately, 132 (29.7%) had reports of positive resectional margins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ponholzer et al 11 reported that marking the PE of biopsy cores and the positivity of PE could increase the risk of positive surgical margins in prostatectomy specimens. Their study involved 445 patients, of whom 174 (39.1%) had positive PE, and ultimately, 132 (29.7%) had reports of positive resectional margins.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Some researchers have previously proposed new parameters such as the distance to the tumor (DTT), to assess the presence of ECE based on prostate biopsy cores. 11 , 12 However, there are limitations in understanding the sole function of DTT in this context. Therefore, our study aims to reassess the practicality of DTT in identifying pathological ECE in comparison with MRI results.…”
Section: Introductionmentioning
confidence: 99%